Eliza hamilton ebook The extraordinary life and times of the wife of alexander hamilton. - Mazzeo, Tilar J. (2018)
From the New York Times bestselling author of Irena's Children comes a "vivid, compelling, and unputdownable new biography" (Christopher Andersen, #1 New York Times bestselling author) about the extraordinary life and times of Eliza Hamilton, the wife of founding father Alexander Hamilton, and a powerful, unsung hero in America's early days. Fans fell in love with Eliza Hamilton—Alexander Hamilton's devoted wife—in Lin-Manuel Miranda's phenomenal musical Hamilton . But they don't know her full story. A strong pioneer woman, a loving sister, a caring mother, and in her later years, a generous philanthropist, Eliza had many sides—and this fascinating biography brings her multi-faceted personality to vivid life. This "expertly told story" ( Publishers Weekly ) follows Eliza through her early years in New York, into the ups and downs of her married life with Alexander, beyond the aftermath of his tragic murder, and finally to her involvement in many projects that cemented her legacy as one of the unsung heroes of our nation's early days. This captivating account of the woman behind the famous man is perfect for fans of the works of Ron Chernow, Lisa McCubbin, and Nathaniel Philbrick.